WEAR BEHAVIOR OF COMMERCIAL TIRE RUBBER AGAINST MILD STEEL IN DRY, WET AND 3.5% NACL CORROSIVE ENVIRONMENT - Kaiser, Samiul; Kaiser, Mohammad Salim; Ahmed, Sheikh Reaz (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering))
The tribological performance of commercially used tire rubber was evaluated at ambient conditions under dry, wet and 3.5% NaCl corrosive environment. A pin-on-disc apparatus was used for the experiment. Applied load of 2.5N at sliding velocity of 0.246 ms-1 distance ranging from 75m-2650m were used for this study. The results showed that the nature of the wear rate was similar in all environments as initially increases afterwards decreases to more or less a constant value. Moreover, the wear rate in dry environment was significantly higher than that of wet and corrosive environment. Water tends to lubricate the contact, reduce the heat generation as well as for sealing effects thus the wear rate is reduced. Coefficient of friction in wet and corrosive environment showed the lower value due to sealing and lubricating effect between the particles. The damage behaviors of worn surfaces were analyzed by optical microscope and SEM. At dry sliding condition greater voids and holes are observed.